1995
DOI: 10.1111/j.1365-2222.1995.tb01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen allergy in the Bilbao area (European Atlantic seaboard climate): pollination forecasting methods

Abstract: Forecasting pollination can help the allergist to establish the appropriate treatment and advice for patients. Based on previous studies, we have related the climate variables with the grass pollen counts in the search for pollination predictors. By relating the meteorological data of the temperature recorded every 6 h and of the rainfall in hourly periods, together with the daily pollen counts obtained by the Hirst volumetric system, over a period of 3 years, we have tried to predict the start, duration and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 18 publications
0
19
2
Order By: Relevance
“…Indeed, rainfall can alter the shape of a year's pollen curve and can influence peak characteristics, as reported in other works (Norris-Hill and Emberlin 1993, Sánchez-Mesa et al 2005, Kasprzyk and Walanus 2010. Currently, in the area of this study, it does not interfere with the beginning or end dates nor with the length of the season, in contrast with what Antépara et al (1995) observed. The lack of a clear trend in this sense is justified by a different sensitivity of the grass species to rainfall and, in general, water availability (Reddi et al 1988).…”
Section: Discussioncontrasting
confidence: 73%
“…Indeed, rainfall can alter the shape of a year's pollen curve and can influence peak characteristics, as reported in other works (Norris-Hill and Emberlin 1993, Sánchez-Mesa et al 2005, Kasprzyk and Walanus 2010. Currently, in the area of this study, it does not interfere with the beginning or end dates nor with the length of the season, in contrast with what Antépara et al (1995) observed. The lack of a clear trend in this sense is justified by a different sensitivity of the grass species to rainfall and, in general, water availability (Reddi et al 1988).…”
Section: Discussioncontrasting
confidence: 73%
“…In Madrid, where the climate is dry-continental, Subiza et al (1992) found that the season start was promoted by the pre-seasonal precipitation, but not by the temperature. In Bilbao (Atlantic climate) Antepara et al (1995) observed quite the reverse, ie. precipitation had no effect on the start of grass pollination, but higher pre-seasonal temperature promoted it.…”
Section: Discussionmentioning
confidence: 98%
“…Many authors have forecast the SDP of various plants, using meteorological parameters; regardless of the procedure, temperature was the most frequently used parameter (Lejoly-Gabriel 1978;Niqueux and Arnaud 1981;Törnevik 1982;Richardson and Anderson 1986;Linvill 1990;Andersen 1991;Frenguelli et al 1991;Sutra et al 1992;Larsson 1993;AntØpara et al 1995;Recio et al 1997;Gonzales Minero et al 1999;Garcia-Mozo et al 2000;Orlandi et al 2002). On rare occasions, radiation or evapotranspiration (Durand 1967), or sometimes several meteorological factors like temperature, wind and rainfall (Mandrioli et al 1993;Fornaciari et al 1998;Laaidi 2001a, b) were used.…”
Section: Forecasting Methodsmentioning
confidence: 98%